Pulmonary nodules: a challenging diagnosis during the follow up of cancer patients - Rafael Caparica Bitton; Ricardo Emanuel Oliveira Ramos; Sheila Siqueira; Olavo Feher (University of São Paulo, 2015)
Pulmonary nodules (PN), frequently found on imaging studies, represent a diagnostic challenge during the follow up of cancer patients. However, published data regarding investigation of PNs incidentally found on chest imaging is scarce. The PN may be present at the time of cancer diagnosis, or arise during the treatment or follow-up periods. In the context of the oncologic patient these lesions are quite invariably considered as metastases, what impacts directly on patients treatment and prognosis. The present study reports 2 cases of pulmonary nodules found in two patients already diagnosed with cancer. Case 1 referred to a woman with squamous cell carcinoma and two pulmonary nodules, and in case 2 the patient was diagnosed with duodenal adenocarcinoma. Both patients were submitted to pulmonary biopsies before the oncologic treatment. In both cases the nodules were of infectious origin, what changed significantly the neoplasia staging and the oncologic treatment intention. The authors performed a literature review as well as a discussion about the management of PN in cancer patients.